Analisis Kemampuan Rasio Likuiditas dan Profitabilitas dalam Mengukur Financial Distress - Muhammad Iksan Sopian; Erry Sunarya; Kokom Komariah (COSTING : Journal of Economic, Business and Accounting, 2019)
Financial distress is a condition where the results of the company's performance are unable to meet the company's obligations. The purpose of this research is to find out the effect of Liquidity and Profitability in measuring financial distress in PT .eterindo wahanatama Tbk and PT. Waskita Karya Tbk. The analysis technique used is multiple linear analysis techniques, and for hypothesis testing is a partial statistical test (t test) and simultaneous test (f test). The results of the t test show that liquidity (CR) (X1) has an effect but not significant to financial distress, Profitability (ROA) (X2) has a significant effect on financial distress. Based on the simultaneous F test means that together Liquidity (CR) and Profitability (ROA) have no significant effect on purchasing decisions (Y). Based on the test of the coefficient of determination of 0.354 it can be interpreted that the effect of Liquidity (CR) and Profitability (ROA) on purchasing decisions is equal to 28.4%. The remaining 71.6% is influenced by other factors not explained in this study. Keywords : Liquidity, Profitability, financial Distress.